High‐strength medium‐entropy (Ti, Zr, Hf)C ceramics up to 1800°C. Issue 6 (12th February 2021) - Wang, Xiao‐Fei; Wang, Xin‐Gang; Yang, Qing‐Qing; Dong, Hong‐Liang; Zhang, Cheng; Zhang, Guo‐Jun; Jiang, Dan‐Yu
Abstract: Medium‐entropy (Ti, Zr, Hf)C ceramics were prepared by hot pressing a dual‐phase medium‐entropy carbide powder with low oxygen content (0.45 wt%). The results demonstrate that the medium‐entropy (Ti, Zr, Hf)C ceramics sintered at 2100°C had a relative density of 99.2% and an average grain size of 1.9 ± 0.6 μm. The flexural strength of (Ti, Zr, Hf)C carbide ceramics at room temperature was 579 ± 62 MPa. With an increase in temperature to 1600°C, the flexural strength showed an increase up to 619 ± 57 MPa, and had no significant degradation even up to 1800°C. The high‐temperature flexural strengths of (Ti, Zr, Hf)C were obviously higher than those of the monocarbide ceramics (TiC, ZrC, and HfC). The primary strengthening mechanism in (Ti, Zr, Hf)C could be attributed to the high lattice parameter mismatch effects between TiC and ZrC, which not only inhibited the fast grain coarsening of (Ti, Zr, Hf)C ceramics, but also increased the grain‐boundary strength of the obtained ceramics.